Pupilometria na investigação de diabetes mellitus tipo II - Silva, Cleyton Rafael Gomes (2018)
Examining human pupillary behavior is a non-invasive, low-cost method for assessing neurological activity. Changes in this behavior are correlated to various health conditions, such as: Parkinson’s, Alzheimer’s, autism and diabetes. In order to obtain information about the pupillary behavior, it is necessary to measure the pupil diameter in procedures that induce pupillary reflexes, known as Pupilometry. Pupillary measurement is made by filming the procedures when applying computer vision techniques for pupil recognition. The objective of this research was to develop an Automated Pupilometry System (SAP) to support the investigation of patients with type II diabetes mellitus. SAP was able to record, induce, and extract 96 pupil features. In the experiment with 15 healthy patients and 16 diabetics, a 94% accuracy in the identification of diabetics type II was obtained, demonstrating the efficiency of SAP for the performance of examinations, and evidencing the potential of pupil use in the investigation of diabetes mellitus type II.